Comprehensive Analysis of mRNA, lncRNA, circRNA, and miRNA Expression Profiles and Their ceRNA Networks in the Longissimus Dorsi Muscle of Cattle-Yak and Yak - Huang, Chun; Ge, Fei; Ma, Xiaoming; Dai, Rongfeng; Dingkao, Renqing; Zhaxi, Zhuoma; Burenchao, Getu; Bao, Pengjia; Wu, Xiaoyun; Guo, Xian; Chu, Min; Yan, Ping; et al. (Frontiers in Genetics, 2021)
Cattle-yak, as the hybrid offspring of cattle (Bos taurus) and yak (Bos grunniens), demonstrates obvious heterosis in production performance. Male hybrid sterility has been focused on for a long time; however, the mRNAs and non-coding RNAs related to muscle development as well as their regulatory networks remain unclear. The phenotypic data showed that the production performance (i.e., body weight, withers height, body length, and chest girth) of cattle-yak was significantly better than that of the yak, and the economic benefits of the cattle-yak were higher under the same feeding conditions. Then, we detected the expression profiles of the longissimus dorsi muscle of cattle-yak and yak to systematically reveal the molecular basis using the high-throughput sequencing technology. Here, 7,126 mRNAs, 791 lncRNAs, and 1,057 circRNAs were identified to be differentially expressed between cattle-yaks and yaks in the longissimus dorsi muscle. These mRNAs, lncRNA targeted genes, and circRNA host genes were significantly enriched in myoblast differentiation and some signaling pathways related to muscle development (such as HIF-1 signaling pathway and PI3K-Akt signaling pathway). We constructed a competing endogenous RNA (ceRNA) network and found that some non-coding RNAs differentially expressed may be involved in the regulation of muscle traits. Taken together, this study may be used as a reference tool to provide the molecular basis for studying muscle development.